Tom Glynn and 'Pickhandle Mary' Fitzgerald: Two Irish Syndicalists in Pre-World War One South Africa. Issue 3 (2nd September 2017) - Cunningham, John
Abstract: Paired in 1911 as Irish 'rebels' by Archie Crawford, their mutual mentor, Tom Glynn and Mary Fitzgerald were pioneers of transnational syndicalism, in South Africa. Arriving separately in the country in 1900, they had taken different routes into labour activism, and despite being close political allies, had markedly different outlooks. She was a feminist, whose syndicalism has been judged 'eclectic'; he, while committed to gender and racial equality, became a proponent of the 'virile syndicalism' of the Chicago-line Industrial Workers of the World. This article discusses their journalism in Johannesburg's Voice of Labour, their roles as leaders in a number of significant labour disputes, the significance of their 'Irishness' in a largely British-oriented milieu, their geographical separation in 1911, and the definitive parting of their political ways on the outbreak of the First World War.